Cell polarity and cytoskeletons—Lesson from the testis. (September 2018) - Wen, Qing; Mruk, Dolores; Tang, Elizabeth I.; Wong, Chris K.C.; Lui, Wing-yee; Lee, Will M.; Xiao, Xiang; Silvestrini, Bruno; Cheng, C. Yan
Abstract: Cell polarity in the adult mammalian testis refers to the polarized alignment of developing spermatids during spermiogenesis and the polarized organization of organelles (e.g., phagosomes, endocytic vesicles, Sertoli cell nuclei, Golgi apparatus) in Sertoli cells and germ cells to support spermatogenesis. Without these distinctive features of cell polarity in the seminiferous epithelium, it is not possible to support the daily production of millions of sperm in the limited space provided by the seminiferous tubules in either rodent or human males through the adulthood. In short, cell polarity provides a novel mean to align spermatids and the supporting organelles (e.g., phagosomes, Golgi apparatus, endocytic vesicles) in a highly organized fashion spatially in the seminiferous epithelium during the epithelial cycle of spermatogenesis. This is analogous to different assembling units in a manufacturing plant such that as developing spermatids move along the "assembly line" conferred by Sertoli cells, different structural/functional components can be added to (or removed from) the developing spermatids during spermiogenesis, so that functional spermatozoa are produced at the end of the assembly line. Herein, we briefly review findings regarding the regulation of cell polarity in the testis with specific emphasis on developing spermatids, supported by an intriguing network of regulatory proteins along a local functional axis. Emerging evidence has suggested that cell cytoskeletons provide the tracks which in turn confer the unique assembly lines in the seminiferous epithelium. We also provide some thought-provoking concepts based on which functional experiments can be designed in future studies.